La importancia de la obra de G. Simondon para la filosofía contemporánea1 - Rodríguez, Pablo Esteban (DoisPontos, 2019)
The article puts G. Simondon’s work in perspective on three axes: its place within what A. Badiou called the “French philosophical moment” (1943-1991), the relationship between Simondonian concepts and some currents of thought today and, finally, the way in which these notions are intertwined within the framework of the general theory of individuation and the technics of the French philosopher. These three axes refer to the need to elaborate a philosophy that is contemporary with the questions posed by its time. According to our hypothesis, Simondon unfolded problems foreign to his time (1924-1989), but very close to ours.Hence his importance for contemporary philosophy. Key‐words: politics; technics; science; humanism; individuation; transindividual.